Comparison of cloud height and depth from atmospheric modelling and ceilometer measurements - Santos, Dina (2009)
In the current study, the cloud base height obtained from the ceilometer measurements, in Evora (south of Portugal), are compared with the results obtained from atmospheric modelling. The atmospheric model adopted is the nonhydrostatic MesoNH model, initiated and forced by ECMWF (European Centre for Medium-Range weather Forecasts) analyses. Also the simulated cloud depth results are presented. The availability of mesoscale modelling for the region, as well as the cloud local vertical distributions obtained from the ceilometer, provide a good opportunity to compare cloud base height and estimate the errors associated. From the obtained results it is possible to observe that the simulated cloud base height values are in good agreement with the correspondent values obtained from the ceilometer measurements.